(Não) leituras de obras literárias em contexto escolar : um estudo de caso a partir de versão integral e adaptações de O cortiço, de Aluísio de Azevedo - Vinter, Ravena Brazil (2017)
The following academic article has part in discussion research group about "Literature and Education" and investigated the relationship between high Literature books and high school students readers in the context of the Public School in Guarapari town (ES). Taking as theoretical contributions and methodological from New Cultural History – according to three different versions of the classic novel “O Cortiço” written by Aluísio Azevedo: a) version with the original full text (2014); b) the adapted version from the collection "is just the beginning" (2009) and c) the adaptation from a comic book (2010). All these versions from the novel are found in the school library. The analyzed research was developed in two moments. The first of a bibliographical-documentary, which sought to understand how the relations between book, reader and reading take place and to think about the way in which some literary adaptations are inserted in the market, including those that integrate programs of distribution of books like PNBE. The second stage was a case study questionnaire and a focus group composed by the second and third class high school students from the analyzed school, which will endeavor to answer the following questions: a) how can be the appropriation of the classic original written and the several adaptations from a novel by the students ?; b) the adapted versions arouse the reader's desire to know the completed text ?; c) how the students create tactics and strategies for (not) taking proposed readings by the school curriculum ?;The classic Literature research was justified by: a) the interest in the History and Literature field, the practices of empirical literary readers and the uses that are made of printed materials, in institutional settings, in tension with official guidelines; b) the needing to think about the ideological economic issues which surround the literary reading in tension with the publishing market; c) our diagnosis - here taken for granted - that many students do not read literary novels suggested by the school curriculum; d) the needing to think the non-literary readings beyond the student’s fault. With research, we know the ways of acquiring the books, some preferences, the main mediators of reading, thus tracing a reader profile of literary reading the school field. We have also come to the conclusion that some adaptations may be classroom reading mediation tools. The authors who guided our studies was: Marisa Lajolo and Regina Zilberman (book and reading in the Brazilian context), Annie Rouxel, Maria Amélia Dalvi and Neide Rezende (literary education), Michel de Certeau, Roger Chartier and Pierre Bourdieu (practices, representations, ownership).